EU Pollinator Monitoring Scheme: a science-policy co-design process - Simon G. Potts; Ignasi Bartomeus; Koos Biesmeijer; Jordi Bosch; Tom Breeze; David Kleijn; Denis Michez; Bas Oteman; Marino Quaranta; Oliver Schweiger; Ante Vujic (Journal of Pollination Ecology)
Response to Krahner et al. (2025) Build the EU Pollinator Monitoring Scheme on robust evidence. Journal of Pollination Ecology 38(13): 183-185. https://doi.org/10.26786/1920-7603(2025)846